Expression of mitotic checkpoint proteins BUB1B and MAD2L1 in salivary duct carcinomas - Ko, Young Hyeh; Roh, Ji Hyeon; Son, Young-Ik; Chung, Man Ki; Jang, Jeon Yeob; Byun, Hayoung; Baek, Chung-Hwan; Jeong, Han-Sin (Journal of oral pathology & medicine, 2010)
J Oral Pathol Med (2010) 39: 349–355 Objective:  Defects in the mitotic checkpoint lead to aneuploidy and might facilitate tumorigenesis. However, the ploidy status in salivary duct carcinoma (SDC) has been reported to play limited role in prediction of prognosis. Thus, we need more reliable markers to reflect the rapid tumor progression in SDCs. We aimed here to investigate the expression of mitotic checkpoint proteins benzimidazole 1 homolog beta (BUB1B) and mitosis arrest‐deficient 2 like 1 (MAD2L1) in SDCs and to determine their possible role as surrogate prognostic markers. Methods:  We analyzed the clinical courses, pathologic findings and immunohistochemical profiles of mitotic checkpoint proteins (BUB1B and MAD2L1) in 27 pathologically confirmed SDCs. The expression status of BUB1B and MAD2L1 was compared with clinicopathologic factors and other molecular markers, such as TGF‐beta, c‐erb‐B2, androgen receptor, vascular endothelial growth factor, and epidermal growth factor receptor, for prognostic significance. Results:  High BUB1B expression was detected in 25.9% of subjects, and high MAD2L1 expression was in 55.6% of subjects. However, survival analysis revealed that mitotic checkpoint expression did not have prognostic significance in SDCs, nor did the other studied markers. Rather, the clinical variable of N classification at diagnosis (in N+ status, hazard ratio 5.19, 95% CI 1.26–21.32 for disease‐free survival and hazard ratio 7.18, 95% CI 1.09–46.99 for overall survival) was strongly associated with survival and prognosis based on the Cox proportional hazard model. Conclusions:  Mitotic checkpoint proteins appeared to play a limited role in predicting prognosis in SDCs. Further study is required to elucidate the exact role of mitotic checkpoint proteins in SDCs.